A Systematic Review of Recreational Sports Club Management: Participation, Organizational Capacity, and Safety Practices - Novia Rahmadani; Rubiyatno Yatno; Ghana Firsta Yosika (Indonesian Journal of Sport Management, 2025)
Background: Recreational sports are a popular way to maintain physical, psychological, and social fitness. There are many sports options for people to choose from. Here's a concrete scientific overview of recreational sports, based on relevant studies, from a management perspective. Objective: To provide safety, rehabilitation and meaningfulness for sports participants in accordance with their respective goals. Method: Study This is literature review research. The data used is based on in study This Web of Science (WOS) with the keywords used is “recreational sports club management” in sports, 40 articles were found. Restrictions search for 5 years final 20 documents found , coupled with the limitation of articles because they do not discuss , recreational sports club management 20 articles were found. Then done restrictions return in theme sports science found articles as many as 20 articles . Of the 20 articles researchers examine between compatibility abstract with theme study found as many as 14 articles . From 14  articles Then reviewed And analyzed. Results: Research shows that in recreational sports management, some people participate in recreational sports for fun, motivation, to enjoy their free time, or to seek a challenge. Some sports commonly participated in as recreational sports include soccer, hockey, cycling, golf, and fishing . Conclusion: Achieving optimal sports performance requires a strong link between injury prevention, a structured training program, and good management support. Implications and Recommendations: To achieve optimal sports performance, an integration of injury prevention, a well-planned training program, and good management support is necessary